Infant, neonatal, and postneonatal mortality trends in a disaster region and in Japan, 2002-2012: a multi-attribute compositional study - Ai Tashiro; Honami Yoshida; Etsuji Okamoto (BMC, 2019)
Abstract Background The reductions achieved in infant mortality in Japan are globally regarded as remarkable. However, no studies in Japan have classified infant mortality trends into neonatal and postneonatal or considered regional issues. This study aimed to explore trends in neonatal and postneonatal deaths, both overall for Japan and in a region affected by a natural disaster. Methods Drawing on national infant death data, we used a multi-attribute compositional study design to examine all infant deaths occurring in a region affected by a disaster (Tohoku, which consists of Iwate, Miyagi, and Fukushima) between 2002 and 2012. We used conjoint analysis to clarify the associations between infant and maternal characteristics and age of infant death. Results We obtained data of a total of 31,012 infant deaths between 2002 and 2012, which included 1450 from Tohoku. Infant mortality rates in Japan overall declined over the period but increased in 2011. There were more postneonatal (29-364 days post-birth) than neonatal (0-28 days post-birth) deaths. Infant deaths in Tohoku declined slightly overall, with a fluctuation in 2011. In Tohoku, the trends in postneonatal death rates were similar; the overall rates for males increased, but those for females decreased in 2011. We found that the cause and place of infant death differed by gender for neonatal and postneonatal deaths in both Japan in general and Tohoku. The conjoint analysis showed that most variables affected the age of postneonatal death. The factor with the largest influence on the variation in infant death age was gestational week (55.5%). A maternal gestational week ≤36 was linked to an average age at death of 43.4 days, and > 37 was linked to an average of 83.7 days. Conclusions In Japan, infant death rates have declined steadily over the past 10 years. The recent trends indicated that postneonatal death rates were higher than neonatal rates, especially in Tohoku. However, not much attention has been focused on postneonatal deaths in Japan. Our findings may help health planners to prioritise work on the factors that are linked to infant deaths in the neonatal and postneonatal periods. Trial registration Not applicable.